Upper Digestive Hemorrhage at Hospital Maciel. Descriptive prospective study - Trostchansky, Julio; Cardozo, Sandra; Laurini, Marcelo; Alvarez, Pilar; Machín, Mariela; Derboghosian, Alejandro; Delgado, Juan; Scelza, Alfredo; Lepera, Roberto; Pradines, Laura; et al. (Cirugía del Uruguay, 2002)
Prospective descriptive study of patients hospitalized with high digestive haemorrhage (HDH) in the Emergency Unit of Maciel Hospital between April 2000 and October 2001. The most frequent cause of HDH was the existence of peptic gastroduodenal lesions and this population is taken as the center for statistical analysis.